SUSTAINABLE ISLAMIC EDUCATION LEARNING WITH CONNECTIVISM APPROACH - Albert, Albert; Irwandi, Irwandi; Husni, Arman; Pranata, Hamdi (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
Education institutions can adopt various pedagogical approaches, principles and methods used by other  training institutions in continuous learning. These methods may include utilizing digital technology and online communication to facilitate distance learning and quick access to relevant information. This research empirically explores the principles of connectivism implemented in the learning and teaching conducted online at Ma'had Aly Integrated Pesantren Serambi Mekkah Padangpanjang, West Sumatra Province. Types of research is qualititaive ,and narrative descriptive as research analysis techniques. The research findings show that connectivism approach can be a suitable conceptual framework and motivate mahasantri to develop knowledge through digital, discussion and social networking with the concept of sustainability. The principles of connectivism can help musyrif to develop a learning environment where mahasantri can add to their understanding and prior knowledge through online interaction and by accessing digital knowledge sources.